Heparin-induced thrombocytopenia associated with low-molecular-weight heparin: clinical feature analysis of cases and pharmacovigilance assessment of the FAERS database - Liu, Leping; Zheng, Hong; Chen, Shanshan; Wang, Shengfeng; Yang, Minghua (Frontiers in Pharmacology, 2023)
Background Unfractionated heparin (UFH) and low molecular weight heparin (LMWH) are commonly used anticoagulants for the management of arterial and venous thrombosis. However, it's crucial to be aware that LMWH can, in rare cases, lead to a dangerous complication known as heparin-induced thrombocytopenia (HIT). The objective of this study was to evaluate the pharmacovigilance and clinical features of HIT associated with LMWH, as well as identify treatment strategies and risk factors to facilitate prompt management.We extracted adverse events report data from FDA Adverse Event Reporting System (FAERS) database for pharmacovigilance assessment. Case reports on LMWHs-induced HIT to March 20, 2023 were collected for retrospective analysis.Results Significantly elevated reporting rates of HIT were shown in adverse events (AEs) data of LMWHs in FAERS database, while tinzaparin had a higher PRR (Proportional Reporting Ratio) and ROR (Reporting Odds Ratio) than other LMWHs indicating a greater likelihood of HIT. Case reports analysis indicated that a total of 43 patients showed evidence of LMWHs-induced HIT with a median onset time of 8 days. Almost half of events were caused by enoxaparin. LMWHs were mainly prescribed for the treatment of embolism and the thromboprophylaxis of joint operation.Patients with a history of diabetes or surgery appeared to be more susceptible to HIT. Clinical symptoms were mostly presented as thrombus, skin lesion and dyspnea. Almost 90% of the patients experienced a platelet reduction of more than 50%, and had a Warkentin 4Ts score of more than six, indicating a high likelihood of HIT. In all patients, the LMWHs that were determined to be the cause were promptly withdrawn. Following the discontinuation of LMWHs, almost all patients were given alternative anticoagulants and eventually achieved recovery.Conclusion LMWH-induced HIT is rare but serious, with increased risk in patients with diabetes or a surgical history. Prompt recognition and management are crucial for the safe use of LMWHs.